Functional fluoro substituted tetrakis-metallophthalocyanines: Synthesis, spectroscopy, electrochemistry and spectroelectrochemistry - KOCA, ATIF (ELSEVIER SCIENCE SA, 2008)
In this study, electron-withdrawing fluoro-functional ligand and its tetrakis 2,9,16,23-4-(2,3,5,6-tetrafluoro)-phenoxy-phthalocyaninatometal (II) complexes, (ZnPcOBzF(16), CuPcOBzF(16) and CoPcOBzF(16)) (Bz: benzene) which are organo-soluble have been prepared. Their structures were confirmed by elemental analysis, FT-IR, H-1 NMR, UV/vis and MS (Maldi-TOF) spectral data. Electron-withdrawing fluorine atoms on 2,3,5,6-position of benzene at the peripheral sites increases the solubility of the tetrakis-metallophthalocyanines. The cyclic voltammetry and differential pulsed voltammetry of the complexes show that while CuPcOBzF(16) and ZnPcOBzF(16) give ligand-based reduction and oxidation processes, CoPcOBzF(16) gives both ligand and metal-based redox processes, in harmony with the common MPc complexes. Spectroelectrochemical measurements confirm the assignments of the complexes. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: phthalocyanines; fluorine; electron-withdrawing; Maldi-TOF; aggregation; spectroelectrochemistry; ELECTRICAL-PROPERTIES; PHTHALOCYANINES; COBALT